PENERAPAN ENTREPRENEURIAL MARKETING DALAM MENINGKATKAN PENJUALAN (STUDI PADA BISNIS MEGAWARNI.ORI) - Ayesha Anzani Putri Dinanti Gunawan; Margo Purnomo; Raden Marsha Aulia Hakim (JURNAL LENTERA BISNIS, 2024)
Megawarni.ori is one of the online-based businesses engaged in the Muslim fashion industry. This research aims to obtain information and a more concrete picture of the application of Entrepreneurial Marketing in increasing sales conducted by Megawarni.ori. The method used in this research is qualitative with a descriptive research type to describe in detail how the application of Entrepreneurial Marketing dimensions, which consists of proactiveness, opportunity focus, customer intensity, innovativeness, risk management, resource leveraging, and value creation is carried out. The data collection techniques were conducted through interviews with six informants and documentation studies. The results of this study indicate that the application of Entrepreneurial Marketing carried out by Megawarni.ori is quite effective, by applying the seven dimensions of Entrepreneurial Marketing Megawarni.ori can survive in a dynamic business environment and support its efforts in increasing sales.